Factors influencing the performance of cement emulsified asphalt mortar – A review. (12th April 2021) - Jiang, Shunjun; Li, Jiusu; Zhang, Zhu; Wu, Hongshan; Liu, Guanlan
Highlights: CEAM combines the excellent properties of both cement and asphalt. The influencing factors on CEAM performance are summarized. Future research is recommended to develop sustainable CEAM. Abstract: Cement emulsified asphalt mortar (CEAM) is an essential component in the ballastless slab track system. It is a semi-rigid composite material consisting mainly of hardened cement paste and demulsification asphalt, possessing the advantages of both ordinary Portland cement and asphalt. Its primary functions include: supporting structures, adjusting the slab track's geometry during construction, and dissipating/reducing orbital vibration. In this review, the preparation technology of CEAM was introduced at first. Subsequently, the hardening mechanism between asphalt emulsion and cement in CEAM was summarized. Meanwhile, the influence of asphalt emulsion type and dosage, sand to cement ratio (S/C), water to cement ratio (W/C), common auxiliary additives, and temperature on the properties of CEAM were compared and analyzed. This current review concludes that the most significant influence on CEAM performance is the mass ratio of asphalt to cement. With the increase of asphalt content, hardened cement asphalt paste (CA paste) would show two different overall mechanical properties. Besides, the effects of the S/C ratio and W/C ratio on high strength CEAM are not the same as that of low strength CEAM. Future research is recommended: to develop sustainable CEAM without prejudice to the performance; and to further analyze the interaction mechanism between emulsified asphalt and cement materials from the microscopic perspective.